A Cultural Sensitivity in Antenatal Care for Muslim Women in Eswatini: A Case Report : Addressing Cultural Competence in Antenatal Services - Mkhonta, Zama; Huang, Mei-Chih; Hsu, Yu-Yun (Alta Dharma Publisher, 2025)
Introduction: Antenatal care is crucial for safeguarding maternal and fetal health. However, systemic and cultural barriers disproportionately affect minority populations, including Muslim women, in Eswatini, a predominantly Christian country. Addressing these challenges is essential to achieving equitable and culturally responsive healthcare. Objective: This case report describes the cultural sensitivity challenges and ethical dilemmas encountered in providing antenatal care to Muslim women in Eswatini. Method: Researchers used a case report approach to examine the experiences of three pregnant Muslim women over six weeks at a resource-limited public hospital. The analysis, guided by Leininger’s Transcultural Nursing Theory, focused on clinical interactions, environmental challenges, and systemic barriers, incorporating nursing diagnoses to contextualize the findings within a care framework. Result: The case identified significant barriers to culturally sensitive antenatal care, including inadequate privacy, limited access to female healthcare providers, and insufficient cultural competence among staff. These issues contributed to emotional distress, discomfort, and reduced patient engagement. Interventions such as private examination spaces, prioritizing female providers, and mandatory cultural competence training showed promise but were inconsistently applied due to staffing and resource constraints, limiting their overall effectiveness. Conclusion: Significant cultural and systemic barriers hinder the delivery of culturally sensitive antenatal care for Muslim women in Eswatini. Recommendations: Maternal healthcare systems are encouraged to integrate cultural competence training, enhance privacy infrastructure, and adopt gender-sensitive practices to promote equitable and culturally responsive care. Keywords: Antenatal care, Cultural Sensitivity, Ethical Dilemmas, Privacy, Transcultural Care